Profile of Students' Science Process Skills in Science Learning in Junior High School: Profil Keterampilan Proses Sains Siswa Dalam Pembelajaran IPA di Sekolah Menengah Pertama - Evi Dwi Rahayu; Nur Efendi (Universitas Muhammadiyah Sidoarjo, 2021)
Science process skills are basic skills that students must have to be able to master and apply the scientific method in everyday life. The importance of mastering science process skills is because it is very influential on student learning outcomes. This study aims to describe the profile of students' science process skills in science learning. This research method uses quantitative methods with a survey approach. The location of the research was carried out at SMPN 3 Taman, Sepanjang, Sidoarjo. The data collection technique used is a test that has been tested for validity. From the results of the study showed that the science process skills of class VII students obtained an average of 51 in the sufficient category. class VIII obtained an average of 46 in the sufficient category. class IX obtained an average of 67 in the good category. From the results of data calculations using the One Way Anova test, the results obtained are Fcount (6.412476) > Fcrit (3.554557) and P-value (0.007895) < (0.05). So it can be stated that Ha is accepted and H0 is rejected. With a 95% confidence level and using a significance level of 5%, it can be stated that there is a difference in the average grades of the VII, VIII, and IX grades of the KPS test results.